Autologous BMAC Therapy Improves Spinal Degenerative Joint Disease in Lower Back Pain Patients - El-Kadiry, Abed El-Hakim; Lumbao, Carlos; Rafei, Moutih; Shammaa, Riam (Frontiers in Medicine, 2021)
Spinal degenerative joint disease (DJD) is associated with lower back pain (LBP) arising from the degeneration of intervertebral discs (IVD), facet joints, intertransversarii muscles, and interspinous ligaments among other anatomical structures. To circumvent the socioeconomic burdens and often-problematic surgical options imposed by DJD therapy, cell-based biologic modalities like bone marrow aspirate concentrate (BMAC) have been investigated in preclinical and clinical settings, mostly for IVD degeneration (IDD), with encouraging outcomes. In this study, we evaluated the differences in therapeutic benefits of BMAC between IVD- and facet joint-originating chronic LBP. Eighteen patients diagnosed with chronic LBP met the selection criteria. Following discography and provocation testing, 13 patients tested positive and were assigned into IDD-associated LBP (1st arm), while the remaining 5 tested negative and were assigned into facetogenic LBP (2nd arm). Autologous BMAC was injected intradiscally in the 1st arm, while the 2nd arm received posterior spinal chain injections. No procedure-related serious events ensued. Clinical improvement was evaluated over 12 months based on pain and functionality questionnaires (VAS, BPI, RAND-36), opioid use, and changes in disc parameters assessed by magnetic resonance imaging (MRI). Ameliorated VAS and BPI scores differed significantly between both arms in favor of IDD patients who also took significantly less opioids. Average RAND-36 scores showed no significant difference between groups albeit a trend suggesting improvement was observed in IDD patients. MRI scans conducted on IDD patients demonstrated marked elevation in disc height and spinal canal space size without worsening disc quality. Overall, this is the first study investigating the potency of BMAC as an IDD treatment in Canada and the first globally for addressing facetogenic pain using cellular therapy.